Significant decrease of photovoltaic power production by aerosols. The case of Santiago de Chile. (April 2020) - Del Hoyo, Mirko; Rondanelli, Roberto; Escobar, Rodrigo
Abstract: Santiago de Chile frequently suffers from atmospheric pollution that contributes to the decrease of solar irradiance on the surface, leading to losses in the energy output of photovoltaic systems. In this study, a simple model is used to estimate the effect of aerosols on the solar irradiance over the city throughout the year, using as input AERONET sunphotometer data and other in-situ measurements. The results show reductions of 3.5% and 14.1% for global horizontal and direct normal irradiance respectively and an increase of 35.4% for diffuse horizontal irradiance between the actual condition in Santiago and a hypothetical atmosphere free of aerosols. These effects translate approximately to an annual difference in the energy output of −7.2% and −8.7% for monocrystalline and amorphous silicon PV technologies respectively, and an annual difference of −16.4% for a CPV technology, showing that aerosols can have a significant effect on the photovoltaic energy production. Highlights: Aerosols produce a significant decrease of incoming solar irradiance in Santiago. This reduction also translate to less power output using different PV technologies. Observations and a model were used to estimate the irradiance and PV power year long. Losses due to the atmospheric column of aerosols depends on the PV technology.